Quantitative Analysis of Plant Growth Exposed to Electric Fields - Hussein Ahmad; Mohd Hafizi Ahmad; Noor 'Aliaa Awang; Izzah Hazirah Zakaria (Universitas Ahmad Dahlan, 2016)
Electromagnetic radiations present in the environment has a profound effect on the growth of vegetable plant primarily grown under the high power transmission lines. The high electric field generated due to ultra high voltage causes the increase and reduction in the size of the plants. Numerous research have been carried out to investigate the effect of electric field on the plants. However, the knowledge in term of quantitative analysis on the effect of electric field on the growth of vegetables is not entirely understood. Thus, this paper presents a study conducted to investigate the effect of high voltage DC electric fields on the young vegetables growth namely ‘Choy Sam’ and bean sprout. The experimental setup was designed which composed of two parallel plate electrodes. This research was focused on the percentage of germination and growing rate of young vegetables. The growth of the young vegetables during exposure was calculated by using statistical methods. The analysis of the results showed that the electric fields and the electric fields treated water have influenced the germination rate and height of stems of both young vegetables causing the increase in stem height.